Isolation and identification of Naphthoquinones from Euclea natalensis with activity against Mycobacterium tubercolosis, other pathogenic bacteria and Herpes simplex virus - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2013)
Thesis (DPhil (Plant Physiology))--University of Pretoria, 2007.